2021
DOI: 10.4414/smw.2021.20513
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure balloon dilatation for the treatment of primary obstructive megaureter: is it the first line of treatment in children and infants?

Abstract: AIMS OF THE STUDY:To evaluate the efficacy of highpressure balloon dilatation (HPBD) as treatment of primary obstructive megaureter (POM) in paediatric patients, we analysed the data of our institute from June 2018 to September 2019.METHODS: 14 patients, aged 5 months to 5 years, with POM were treated with HPBD. All patients had a distal ureter dilatation greater than 7 mm associated with obstructive features on a mercaptoacetyl triglycine-3 diuretic renogram scan, and a voiding cystourethrogram without vesico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
0
15
0
3
Order By: Relevance
“…1 ). 13 studies were included in the analysis [ 10 22 ]. All included studies were retrospective in design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ). 13 studies were included in the analysis [ 10 22 ]. All included studies were retrospective in design.…”
Section: Resultsmentioning
confidence: 99%
“…Out of 13 studies included, ten reported routinely using a double-J stent for three weeks to 3 months after HPBD [ 10 , 11 , 13 , 15 , 16 , 18 22 ]. Two authors [ 12 , 14 ] reported that a double-J was not inserted routinely.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dilating balloon was insufflated until the narrow ring disappeared, and a double-J stent was positioned and withdrawn 2 months after the procedure. Short-term follow-ups have yielded various success rates (46% to 100%) after the first dilatation and rates of hydronephrosis improvement (76% to 100%) (as shown in Table 3 ) ( 58 - 60 , 62 , 64 , 68 , 69 ). Moreover, long-term follow-ups of 6.9 and 10.3 years also present high overall success rates of 95% and 100% respectively ( 63 , 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since EBD of obstructive megaureter was first reported by Angulo et al in 1998 (56), many urologists have published their experiences and outcomes (Table 3) (55,(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69). EBD was traditionally performed under fluoroscopic monitoring.…”
Section: Ebdmentioning
confidence: 99%